STP ANALYSIS (SEGMENTING, TARGETING, POSITIONING) AND SWOT ANALYSIS IN DIGITAL MARKETING STRATEGIES INFACING BUSINESS COMPETITION AT BT BATIK TRUSMI CIREBON - Agustian, Adheflee Muhammad; Syaeful Bakhri; Moh. Mabruri Faozi (Journal on Islamic Economics, Finance & Banking [Z-CONOMICS], 2025)
The advancement of digital technology compels businesses to adapt through digital-based marketing strategies. This study aims to analyze the digital marketing strategy of BT Batik Trusmi Cirebon using the STP (Segmenting, Targeting, Positioning) framework and SWOT analysis to address competitive challenges. A descriptive qualitative approach was employed, with data collected through in-depth interviews with the Digital Marketing and Office Supervisors, direct observation of digital marketing activities, and documentation from social media, marketplace, and internal reports. Data validity was ensured using triangulation of sources and methods. The findings indicate that BT Batik Trusmi applies various digital marketing strategies, including SEM, SEO, Social Media Marketing, Display Advertising, Affiliate Marketing, Content Marketing, and Viral Marketing, which positively contribute to brand awareness and sales growth. Through STP, the company applies a selective specialization targeting strategy and positions itself as the largest batik center with a one-stop shopping concept. SWOT analysis results, with IFAS scoring 4.40 and EFAS 4.30, place the company in Quadrant I (Growth Oriented Strategy), suggesting an aggressive (S–O) strategy. Practically, this research highlights the importance of integrated and consistent digital marketing to strengthen competitiveness. The originality lies in combining STP and SWOT frameworks to provide a comprehensive evaluation of digital marketing strategy in the batik industry.